The South Beach diet : the delicious, doctor-designed, foolproof plan for fast and healthy weight loss - Agatston, Arthur. 4 0 16; 5 (Emmaus, Penn. : Rodale :;Distributed to the Book trade by St. Martin's Press, 2003)
A renowned cardiologist discusses the importance of understanding the glycemic index values of foods and presents a weight-loss program that includes meal plans and recipes.
Understanding the South Beach Diet --;Meal Plans and Recipes. Part 1;Part 2
Previously a hardcover ed. was published by: New York : Random House, 2003.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Reducing diets.;Glycemic index. -- 20; 20; 2